Tailoring fuel properties using jatropha, palm and coconut biodiesel to improve CI engine performance and emission characteristics - Iqbal, Md. Arbab; Varman, Mahendra; Masjuki, Haji Hassan; Kalam, M.A.; Hossain, Sajjad; Sayeed, Imtenan (Elsevier, 2015)
Biodiesel can be used effectively as engine fuel despite several limitations in its fuel properties. A set of experiment was conducted to improve fuel properties by blending palm biodiesel (PB) with coconut biodiesel (CB) and jatropha biodiesel (JB). MATLAB optimization tool was used to identify the optimum blend ratio for good fuel properties. A linear relationship among fuel properties was considered for MATLAB coding. The resulting optimum blend ratio and the equations of the MATLAB code were used to predict the fuel property values and were compared with the experimental values of the optimum blend fuel properties. Two new biodiesel blends were developed, namely, the optimum blends of palm coconut (PC) biodiesels and jatropha palm coconut (JPC) biodiesels. Both biodiesels demonstrated overall improved fuel properties compared with those of the individual biodiesels presented in the blends. Engine performance and emission were tested using 20 blend of each biodiesel (lB, PB, CB, PC, and JPC) with petroleum diesel (OD). The engine performance and emission characteristics for the PC and JPC blends were then compared with those of OD. The average engine power for the blend of 20 JPC biodiesel and 80 OD (JPC20) was maximum at lower fuel consumption than the blend of 20 PC biodiesel and 80 OD (PC20) at full load condition. The emission characteristics of JPC20 were also comparable to or lower than those of OD, except for HC. However, when both engine performance and emission were considered, JPC20 was found to be the best fuel compared with OD and other fuel blends. (C) 2015 Elsevier Ltd. All rights reserved.